Inflammatory Biomarkers in Childhood Arterial Ischemic Stroke: Correlates of Stroke Cause and Recurrence. Issue 9 (September 2016) - Fullerton, Heather J.; deVeber, Gabrielle A.; Hills, Nancy K.; Dowling, Michael M.; Fox, Christine K.; Mackay, Mark T.; Kirton, Adam; Yager, Jerome Y.; Bernard, Timothy J.; Hod, Eldad A.; Wintermark, Max; Elkind, Mitchell S.V.
Abstract : Background and Purpose—: Among children with arterial ischemic stroke (AIS), those with arteriopathy have the highest recurrence risk. We hypothesized that arteriopathy progression is an inflammatory process and that inflammatory biomarkers would predict recurrent AIS. Methods—: In an international study of childhood AIS, we selected cases classified into 1 of the 3 most common childhood AIS causes: definite arteriopathic (n=103), cardioembolic (n=55), or idiopathic (n=78). We measured serum concentrations of high-sensitivity C-reactive protein, serum amyloid A, myeloperoxidase, and tumor necrosis factor-α. We used linear regression to compare analyte concentrations across the subtypes and Cox proportional hazards models to determine predictors of recurrent AIS. Results—: Median age at index stroke was 8.2 years (interquartile range, 3.6–14.3); serum samples were collected at median 5.5 days post stroke (interquartile range, 3–10 days). In adjusted models (including age, infarct volume, and time to sample collection) with idiopathic as the reference, the cardioembolic (but not arteriopathic) group had higher concentrations of high-sensitivity C-reactive protein and myeloperoxidase, whereas both cardioembolic and arteriopathic groups had higher serum amyloid A. In the arteriopathic (but not cardioembolic) group, higher high-sensitivity C-reactive protein and serum amyloid A predicted recurrent AIS. Children with progressive arteriopathies on follow-up imaging had higher recurrence rates, and a trend toward higher high-sensitivity C-reactive protein and serum amyloid A, compared with children with stable or improved arteriopathies. Conclusions—: Among children with AIS, specific inflammatory biomarkers correlate with cause and—in the arteriopathy group—risk of stroke recurrence. Interventions targeting inflammation should be considered for pediatric secondary stroke prevention trials. Abstract : Supplemental Digital Content is available in the text.